The names [large type] - Knapp, Florence (Read with Jenna., 2025)
"A dazzling debut that asks: Can a name shape the course of a life? In the wake of an enormous, history-making storm, Cora sets off with her nine-year-old daughter, Maia, to register her son's birth. Her husband Gordon, a local doctor, respected in the community but a terrifying and controlling presence at home, intends for her to follow his family tradition going back generations, and name the child Gordon. But on the journey there, Cora wonders if it's right to impose the burden of this name and its legacy onto her tiny newborn son. She herself has Julian in mind, and Maia offers up her own suggestion: Bear. What follows are three alternate and alternating versions of both Cora's life and her young son's life shaped by her brave, last-minute choice of name. Spanning thirty-five years, the novel draws us in from the first page, as we follow three unforgettable journeys of one young man, but also his mother, grandmother, and sister. In richly layered prose, The Names explores the painful ripple effects of domestic abuse, the messy ties of family, and the possibilities of autonomy and healing. With exceptional sensitivity and depth, Knapp draws us into the story of one family told through a prism of what-ifs, and shows us what we each can do with the "one precious life" we are given. The Names's brilliantly imaginative structure and storytelling, and the emotional, gut-wrenching power of the book itself, are certain to make it a modern classic."--